2012
DOI: 10.1080/19443994.2012.661270
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and fate of perfluorinated compounds (PFCs) in a pilot constructed wetland

Abstract: A B S T R AC TRemovals of perfl uorooctanoic acid (PFOA) and perfl uorooctane sulfonate (PFOS) in pilot-scale constructed wetland were investigated in this study. Phytoextraction by four aquatic plants (Hygrophila pogonocalyx Hayata, Ipomoea aquatic Forssk, Ludwigia (x) taiwanensis and Eleocharis dulcis) and sorption onto soil were determined. Both PFOA and PFOS were fairly phytoextracted by four aquatic plants; the uptake capacity was found in the following order: Hygrophila pogonocalyx Hayata > Ipomoea aquat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…That wetland plants are more efficient to remove pollutants than terrestrial plants have earlier been discussed by Fritioff & Greger [20] for heavy metals and Bergquist & Greger [21] for arsenic. Carex rostrata removed 63% PFOS and 42% PFOA after 12 days (Table 2), which can be compared with data by Chen et al (2012) [11] showing removal of up to 82% for PFOA and 95% for PFOS by wetland plants, especially Hygrophila pogonocalyx (Hayata), 15 days after treatment. The higher removal value in the work by Chen et al [11] might be due to the fact that sediment was included since, in addition to phytoextraction removal works by sorption onto sediment.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…That wetland plants are more efficient to remove pollutants than terrestrial plants have earlier been discussed by Fritioff & Greger [20] for heavy metals and Bergquist & Greger [21] for arsenic. Carex rostrata removed 63% PFOS and 42% PFOA after 12 days (Table 2), which can be compared with data by Chen et al (2012) [11] showing removal of up to 82% for PFOA and 95% for PFOS by wetland plants, especially Hygrophila pogonocalyx (Hayata), 15 days after treatment. The higher removal value in the work by Chen et al [11] might be due to the fact that sediment was included since, in addition to phytoextraction removal works by sorption onto sediment.…”
Section: Discussionmentioning
confidence: 59%
“…The removal of PFOS and PFOA increased with time, where the removal by C. rostrata increased with time at least up to 12 days (Figure 1). Also, Chen et al [11] found higher removal of PFOS and PFOA with time from aquatic plants. It is less likely that the increase in removal is due to higher uptake with time; since the plants showed saturation in the uptake rates after 8 days when the plant concentration was stabilized [11].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…HSSF wetlands are mainly designed to treat primary settled domestic and municipal wastewaters of medium and small communities, nevertheless, at present these systems are also used to treat many other types of wastewaters including industrial and agricultural effluents, landfill leachate, urban and highway runoff, etc. [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the calculation with software MarvinSketch 5.12.4 and the reported data [42], the octanol-water partition coefficients (Log Kow) are from 2.50 to 5.11 for PFOA and 4.13 to 5.43 for PFOS, respectively, indicating that PFOA and PFOS may tend to be easily dissolved in non-polar solvents. Thus, it seemed difficult to separate PFOA and PFOS from the lipids which were abundant in the samples if merely non-polar solvents were used.…”
Section: Sample Preparationmentioning
confidence: 99%